e-LD : A Collaborative and Online e-Learning Design Authoring Tool Based on IMS-LD Specification - Mhouti, Abderrahim El; Nasseh, Azeddine; Erradi, Mohamed (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, with the evolution of e-learning technologies, there is an urgent need for the design, development, reuse and sharing of online courses and contents as standard learning objects. To build this courses, this requires the use of creation tools, called “authoring tools”, which manifest, in most cases, a complexity of use for teachers authors. The aim of this work is to develop an authoring tool for constructing learning objects, tool targeted at supporting teachers instructors in implementing educational contents. The authoring environment, called “e-LD (e-Learning Design) Authoring Tool” is based on the methods of Instructional Design and Learning Design, particularly the IMS-LD specification that offers an explicit separation of "activities" and "resources" by specifying the semantic relations linking them. In addition, e-LD tools introduces an aspect of online and collaborative Learning Design : the process of e-Learning Design is done collaboratively by integrating interaction tools inspired from collaboration on Web 2.0 applications. Firstly, the paper justify the choice of IMS-LD as basic model to construct learning objects. Then, this work presents the design and development process of learning objects and describes the steps of the development process. Finally, the paper exposes the adopted technical choices and a first prototype is set up to provide a subjective evaluation of the new framework.